C-reactive protein and Biliary Complications as Independent Predictors of Length of Hospital Stay in Acute Cholecystitis - Aamna Nazir; Ahmad Naeem Akhtar; Raja Sadam Mehmood; Muhammad Idrees; Muhammad Tariq Khan; Muhammad Tariq Khan; Muhammad Atif Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Acute cholecystitis is a frequent biliary emergency and a variable clinical condition. Identification of factors associated with long hospital stays is crucial to better patient management. The presence of C-reactive protein (CRP) and biliary complications can be important prognosticators of the severity and recovery of the disease. Objective: To assess the independent predictive value of CRP level and biliary complications for the length of hospital stay in acute cholecystitis patients. Materials and Methods: A prospective observational study was done on 200 patients of acute cholecystitis from October, 2025 to March, 2026 in Shifa International Hospital, Islamabad. The clinical parameters, C-reactive protein, biliary complications, and duration of hospital stay were documented and analyzed. Results: CRP levels were significantly higher, and hospital stay was longer in patients with biliary complications. Increased CRP and biliary complications were found to be independent risk factors for longer hospital stay. Conclusion: Measurement and assessment of CRP and biliary complications can be useful for risk stratification and prediction of the length of hospital stay in acute cholecystitis.